Budget institutions and fiscal performance of the Brazilian Federal Government - Ana Carolina Giuberti (EconomiA, 2015)
This article aims to assess the impact of federal budget institutions on the primary deficit of the Brazilian Federal Government from 1985 to 2009, a period marked by important changes in these institutions. Based on the methodology established in the literature on political economy that is linked to the macroeconomic mainstream, three sets of budget indices and their respective sub-indices are constructed, and their behaviour over the period of analysis indicate that the changes made have resulted in institutions that induce greater fiscal discipline. Regarding the effect of these institutions on the fiscal performance, the results allow us to conclude that the institutional changes have contributed to a lower government deficit. – – O presente artigo tem por objetivo avaliar o impacto das instituiç\~oes orçamentárias federais no déficit primário do Governo Federal, no período de 1985 a 2009, período este marcado por importantes mudanças nestas instituiç\~oes. Com base na metodologia estabelecida na literatura de economia política ligada ao mainstream macroeconômico, três conjuntos de índices orçamentários e seus respectivos subíndices s\~ao construídos, e o seu comportamento ao longo do período analisado mostra que as mudanças realizadas resultaram em instituiç\~oes que induzem a uma maior disciplina fiscal. No que tange ao impacto destas instituiç\~oes sobre o resultado fiscal, os resultados permitem concluir que as mudanças institucionais contribuíram para um menor déficit público.
Keywords: H61; H62; 330; Budget institutions; Government; deficit; Budget